Syntax Construct Validity Of Project Based Learning Ofglobal Warming Material - Budiharti, Rini; *, Sutantoro; Aristiyaningsih, Lia (Proceeding of International Conference on Teacher Training and Education, 2016)
The aim of this research is to test construct validity in the syntax development model of Project BasedLearning (PjBL) based on Physics learning in the Global Warming material at Senior High School. This is aÂ quantitative research used Research and Development (R & D) model. The model development that wasÂ used in this research is Borg model and Gall, that is descriptively model, which is showed the steps thatÂ should be followed to create product, in this case in form of syntax of PjBL learning model based scientificÂ approach. The first step of this research was collecting data information related to the need analysis in theÂ field related with implementation of Curriculum 2013 in the Physics learning. As itâs established inÂ curriculum that through learning process in each subject it is hoped that can direct students to implement theÂ concepts which they are got to solve the problems or natural phenomenon through scientific approach. InÂ the Physics learning at Senior High School, PjBL become a one learning model which applicative to theÂ citizen dynamic, for those it is needed to develop a syntax model of PjBL based on scientific approach thatÂ appropriate in learning. Data collection is done by documentation technique, interview, questionnaire, andÂ test. The data collection is in form of qualitative and quantitative data. The datum were considered validÂ through repetition process (iteration) and the data that often appear the being analyse qualitatively throughÂ Miles and Huberman interactive model, that is through data reduction, data display and drawing conclusionÂ in the same time and after data collection process. Data analysis technique that is used was descriptiveÂ qualitative analysis. The result of expert validation stated that the product is appropriate to be tested in theÂ school with some revision. The result shows that the learning syntax that was designed was appropriate toÂ be tested to students with some revision. The test was done, to each test project threat to the big group ofÂ studentsâ amount 32 students. Based on the test result which was conducted it is got the average percentageÂ who achieved passing grade is 84%. So that the product which is created is effective to be implemented inÂ the Physics learning process at Senior High School. The result of this research is in form of syntax model ofÂ PjBL in Physics learning in Global Warming material for students of Senior High School with theÂ characteristics below: (1) Learning syntax that is developed is suited with scientific learning approach (2)Â Global Warming material divides in two projects that is project of The Cause of Global Warming andÂ Reducing Carbon Track (3) Each project has different time allocation, viewed from the comprehensivenessÂ the material and the project that is developed. Then, it can be concluded that the product which is created inÂ this case is in form of syntax model of PjBL based on scientific approach, lesson plan, and studentsâÂ worksheet in the Global Warming material with description of activities cover: 1) Observing andÂ Questionning to the aspect of Basic Question, 2) Experimenting/ Data Collection or Information to theÂ aspect of Designing Project, 3) Associating/ Analysing Data and Information to the aspect of ArrangingÂ schedule and Monitoring students- project progress, 4) Connecting to the aspect of Result test andÂ Evaluating experience; suitable to be implemented in Senior High School Physics learning.